An important role of PHRF1 in dendritic architecture and memory formation by modulating TGF-β signaling - Ting-Wei Shih (Nature Portfolio, 2020)
Abstract PHRF1 is involved in transforming growth factor β (TGF-β) signaling to constrain the formation of acute promyelocytic leukemia (APL) in mouse APL models. PHRF1 also participates in modulating non-homologous end-joining. However, the role of PHRF1 in mammalian dendrite architecture and synaptic plasticity is unclear. Here, we investigated the role of PHRF1 in dendritic formation in the murine hippocampus using Camk2a promoter driven-iCre recombinase to conduct a PHRF1 conditional knockout, namely PHRF1Δ/Δ, in the forebrain region. PHRF1Δ/Δ mice developed normally, but exhibited anxiety-like behaviors and displayed defective spatial memory. Alterations of dendritic complexity in apical and basal dendrites of pyramidal neurons were noticed in PHRF1Δ/Δ mutants. Furthermore, electrical stimulation in the hippocampal CA1 region after the TGF-β1 treatment showed a reduced synaptic plasticity in PHRF1Δ/Δ mice. Immunoblotting analysis indicated that PHRF1 ablation affected the TGF-β signaling. Collectively, our results demonstrate that PHRF1 is important for the dendritic architecture and required for spatial memory formation in the hippocampus.